Metode Pose to Pose Untuk Perancangan Animasi 3D Islami “Ghibah” - Imroatus Tsaany Maghfira; Alroy Rasyid Resan; Firyal Nabila Zalfa; Naufal Bakhtiar Ismail; Veri Verdiansyah; Juniardi Nur Fadila; Fresy Nugroho (Jurnal KomtekInfo, 2022)
In the world of technology and information, the application of technology in terms of visualization on computer graphics is very useful. From all walks of life, especially children, they can learn something Islamic to help study religion, one of which is through an interesting 3D animation. So that the animation movement is smooth and looks real can be done by various methods. In this study, one method is used, namely, the pose to pose method in an Islamic 3D animation design entitled "Ghibah!". The pose to pose technique is a method used in the animation process. The pose to pose method implements basic human movements in 3D animation so that the animation looks real. The design of 3D animation for making characters will use make human tools more often, which will then be imported into Blender software to be designed as a whole.